A combined approach for deposition and characterization of atomically engineered catalyst nanoparticles. (3rd July 2015) - Yang, Q.; Joyce, D. E.; Saranu, S.; Hughes, G. M.; Varambhia, A.; Moody, M. P.; Bagot, P. A. J.
Abstract : The structure and composition of catalytic silver nanoparticles (Ag-NPs) fabricated through a novel gas condensation process has been characterized by Scanning Electron Microscopy (SEM) and Atom Probe Tomography (APT). SEM was used to confirm the number density and spatial distribution of Ag-NPs deposited directly onto standard silicon microposts used for APT experiments. Depositing nanoparticles (NPs) directly by this method eliminates the requirement for focussed ion beam (FIB) liftout, significantly decreasing APT specimen preparation time and enabling far more NPs to be examined. Furthermore, by encapsulating deposited particles before final FIB sharpening, the APT reconstruction methodologies have been improved over prior attempts, as demonstrated by comparison to the SEM data. Progress in these areas is vital to enable large-scale catalyst research efforts using APT, a technique, which offers significant potential to examine the detailed atomic-scale chemistry in a wide variety of catalytic NPs. Graphical Abstract: